Analisis Urban Heat Island untuk Pengendalian Pemanasan Global di Kota Yogyakarta Menggunakan Citra Penginderaan Jauh - Guntara, Ilham; , Drs. Yuli Priyana, M.Si (2016)
Global warming has become a trending topic because it brings a tremendous impact on the earth. It's caused in part by the Urban Heat Island (UHI) phenomenon. Effects of global warming can't be eliminated but can be controlled with various mitigation that bring balance to the ecosystem and environmental quality. This research aims to: 1) Mapping the spatial distributon of LST and UHI in Yogyakarta City, 2) Formulate recommendations of global warming restraint in Yogyakarta City based on spatial analysis of UHI. Spatial Distribution of UHI can be extracted from remote sensing imagery through digital image processing by deriving the Land Surface Temperature (LST) data. Field observations were conducted with purposive sampling method of the physical factors that affect the UHI, such as landcover, landuse, building structure, and green open spaces. Recommendations of global warming restraint were generate through spatial analysis and qualitative analysis of the study data. The result showed UHI data in three time period series (2013-2015). Comparison of three UHI data showed that the temperature differences has detail, varied, and dynamic distribution of values in Yogyakarta City. High temperature difference occurs in open land and various types of buildings with poor green open space conditions. The global warming restraint should be done in areas that have high UHI, such as the expansion of green open space, the application of green roof building, planting of trees, the addition of a green garden city, the application of strict government regulations, the addition of public transport, the application of environmentally-friendly building, and restrictions on private motor vehicles.